Covid-19 Diagnosis Based Android Mobile Application using Certainty Factor Method - Imanuel Sinuraya; Agung Triayudi; Ira Diana Sholihati (SISFOTENIKA, 2020)
Expert Systems are part of a general category of computers known as intelligence. Created Expert System to work on a domain. To make it easier to conclude a problem, however, it requires efficient data to a certain part of basic knowledge, and human thinking procedures to implement knowledge on a given problem. In artificial intelligence, an expert system is a computer system that mimics the decision-making ability of humans who are experts in their fields. The main thrust of artificial intelligence is in the development of computer functions related to human intelligence, such as reasoning, learning, and problem solving, to build a knowledge-based system in the specific field of medicine in the domain for the purpose of diagnosing Covid-19 displayed on mobile devices, information that is quickly and precisely from an expert is needed, can be formulated a problem in the form of diagnosis Covid-19 through the application of an expert system in the form of input symptoms. This is what drives the creation of the Covid-19 diagnostic system using a certainty factor based on Android mobile application.